Are breath-holding spells always innocuous: A case report (Indian Journal of Case Reports, 2024)
The diverse clinical manifestations of Langerhans cell histiocytosis (LCH) present a dilemma to clinicians and pediatricians play an important role in its diagnosis and multidisciplinary approach. LCH, previously known as histiocytosis X, is an uncommon hematological disorder characterized by uncontrolled stimulation and proliferation of normal antigen-presenting cells, Langerhans cells. The purpose of this report is to describe the case of a 7-month-old female child with multisystem involvement who presented with breath-holding spells and to discuss the clinical, radiological, and histopathological features of LCH.